Critical thinking : your guide to effective argument, successful analysis & independent study - Chatfield, Tom, 1980- (Los Angeles ; London : Sage, 2018)
"This helpful book is your personal toolkit for critical thinking. Author Tom Chatfield will show you how to sharpen your critical thinking by developing and practicing this specific set of skills, so you can: Spot an argument and understand why reasoning matters; Discover errors and evaluate evidence; Understand and account for bias; Become a savvy user of technology; and Develop clear, confident critical writing"--Publisher's website.
Welcome to the book! -- What is critical thinking (and why does it matter)? -- The Art and Science of Being Reasonable. Understanding the reasons behind things -- Spelling out arguments and assumptions -- Reasoning with logic and certainty -- Reasoning with observation and uncertainty -- Developing explanations and theories -- Assessing evidence and planning your reading strategy -- Intermission -- Being Reasonable in an Unreasonable World. Getting to grips with rhetoric -- Seeing through faulty reasoning -- Understanding cognitive bias -- Overcoming bias in yourself and others -- Thinking critically about technology -- Putting it all together : critical thinking in study, work and life.
Includes bibliographical references (pages [303]-308) and index.
Keywords: Critical thinking; Logic; Reasoning; Critical thinking; Logic; Reasoning